1979
DOI: 10.2172/1033358
|View full text |Cite
|
Sign up to set email alerts
|

Design, Analysis, and Optimization of RTG for Solar Polar Mission

Abstract: The paper presents the conceptual design of an RTG, employing stacked radioisotope heat source modules and silicongermanium thermoelectric couples, for use on the joint NASA/ESA International SolarPolar Mission, to be launched in early 1983,The use of stacked heat source modules in RTGs requires a structural support system which holds the stack together during launch, but allows it to disassemble when the generator housing melts during reentry. This is a much more difficult support problem than in the case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The study reported last year [3] presented two illustrative RTG designs: a 9-watt design for direct communication to Earth and a 3-watt design for communication through an orbiting relay. Both designs strove to maximize the use of previously developed technology, including the General Purpose Heat Source (GPHS) [4] used in the Galileo and Ulysses RTGs [5]; the SiGe thermoelectric materials employed in the RTGs for the Voyager, LES 8/9, Galileo and Ulysses missions, and the multicouples developed for DOE's Mod-RTG program [6,7]. Modifications were introduced only where necessary to improve the RTG's Impact resistance and to meet other mission requirements.…”
Section: Rtg Designmentioning
confidence: 99%
“…The study reported last year [3] presented two illustrative RTG designs: a 9-watt design for direct communication to Earth and a 3-watt design for communication through an orbiting relay. Both designs strove to maximize the use of previously developed technology, including the General Purpose Heat Source (GPHS) [4] used in the Galileo and Ulysses RTGs [5]; the SiGe thermoelectric materials employed in the RTGs for the Voyager, LES 8/9, Galileo and Ulysses missions, and the multicouples developed for DOE's Mod-RTG program [6,7]. Modifications were introduced only where necessary to improve the RTG's Impact resistance and to meet other mission requirements.…”
Section: Rtg Designmentioning
confidence: 99%
“…The study reported last year [3] presented two illustrative RTG designs: a 9-watt design for direct communication to Earth and a 3-watt design for communication through an orbiting relay. Both designs strove to maximize the use of previously developed technology, including the General Purpose Heat Source (GPHS) [4] used in the Galileo and Ulysses RTGs [5]; the SiGe thermoelectric materials employed in the RTGs for the Voyager, LES 8/9, Galileo and Ulysses missions, and the multicouples developed for DOE's Mod-RTG program [6,7]. Modifications were introduced only where necessary to improve the RTG's Impact resistance and to meet other mission requirements.…”
Section: Rtg Designmentioning
confidence: 99%
“…This arrangement is identical to that use in the 18-module RTGs successfully flown on the Galileo and Ulysses mission. 2 The predicted power profile of the above RTG during the 8.2-year PFF mission is depicted in Figure 2 for three specific fuel options, with respective BOM thermal powers of 254, 234, and 220 watts per heat source module. For each fuel option, the figure shows the BOM efficiency, the optimum RTV voltage, and the BOM and EOM hot- junction temperatures.…”
Section: Introductionmentioning
confidence: 99%